ON CERTAIN PERSIAN HOMONYMOUS WORDS IN ALISHER NAVOI’S EPIC SADDI ISKANDARIY (Eureka Journal of Language, Culture & Social Change, 2026)
This article analyzes the functional features of homonymous words in Alisher Navoi’s epic Saddi Iskandariy. It elucidates that the extensive use of formally identical lexemes in the poet’s works is closely connected with the polysemy and figurative richness characteristic of classical literature. In particular, the context-dependent expression of different semantic layers by homonymous units such as nay, band, and dam is demonstrated through textual examples. The study substantiates the functional role of homonyms in enhancing imagery, melodiousness, and artistic expressiveness in poetic discourse. It also provides a scholarly interpretation of the relationship between homonymous words and the rhetorical devices of tajnis and iyhom, as well as their place in the structure of poetic speech.
Keywords: Homonymy, polysemy, tajnis, iyhom, poetic discourse, semantic layer, artistic imagery.